Production and biochemical characterization of freeze-dried blueberry juice from enzymatically processed berries - E. A. Alekseenko; N. Yu. Karimova; G. V. Semenov; I. S. Krasnova; O. E. Bakumenko (Пищевые системы, 2024)
Production of freeze-dried juice semi-finished products is a promising direction in the technology of processing blueberries. This direction allows complex problem solving regarding seasonality of berry processing with optimization of logistics costs, extension of the geography of sources of raw material supply while preserving high sensory properties of a freeze-dried product. The main advantages of such a product are characteristics determining properties of fresh berries, including taste, color, aroma, nutritional and biological value. The aim of the study was the development of technological solutions to produce freeze-dried blueberry juice from enzymatically processed blueberry pulp, as well as determination of its biochemical characteristics. Chemical (titrimetric and gravimetric) methods and modern physico-chemical methods (HPLC, atomic absorption spectrometry, potentiometric and spectrophotometric methods) were used in the work. As a result of the performed investigations, parameters have been determined for the process of freeze-drying of native blueberry juice: freeze-drying temperature of –23 ±2 °С and pressure of 70–80 Pa, secondary drying at a temperature of 38–40 °С. Duration of the freeze-drying process was 16 hours until reaching the final moisture of 4%. It is shown that freeze-dried juice preserves all quality attributes of the native juice: taste, color and aroma. The native and freeze-dried blueberry juice was characterized by the chemical composition. The profile of flavonoids, anthocyans, phenolic and organic acids, composition of sugars, vitamins and minerals were studied. It has been established that the chosen parameters of freeze-drying ensure preservation of biologically active and minor substances at a level of no less than 77% of the initial content in the native juice. High preservation was demonstrated for quercetin and resveratrol. Losses were 9.6% for epicatechin, 13.7–23.0% for phenolic acids, and 14–22% for vitamins. As a result of juice processing by freeze-drying, an increase was noticed for the content of delphinidin-3-glucoside, cyanidin-3-arabinoside, cyanidin-3-glucoside by 20–35%. The proportion of cyanidin-3-galactoside + delphinidin-3-arabinoside decreased by 65% and that of delphinidin-3-galactoside by 2.85 times. A decrease in the content of macro-elements (up to 6.0%) was established in the freeze-dried juice; more noticeable losses were recorded for micro-elements (up to 14.8%). The results obtained show prospects of using the technology and chosen regimes of freeze-drying in production of freezedried blueberry juice. This technology combines a possibility of producing a manufacturable berry ingredient with maximum preservation of natural biologically active and minor components of berries for using in products of healthy nutrition.